Improved fast marching methods with application in traveltime tomography - Qi, Yingyu (Nanyang Technological University, 2022)
Seismic wave speed and anisotropy provide essential constraints on the Earth’s internal velocity structure and deformation history. The propagation of the seismic wave can be modeled by a Hamilton system in the forward modeling. Then the best fit depth-dependent anisotropy is obtained by the optimal solution of an inverse problem. The numerical accuracy of solving the inverse problem has a significant impact on the resolution and quality of the final tomographic images.